Congenital cataract surgery with intraocular lens implantation in microphthalmic eyes: visual outcomes and complications - Ventura,Marcelo Carvalho (2013)
PURPOSE: To report the visual outcomes and complications of congenital cataract surgery with primary intraocular lens implantation in microphthalmic eyes of children younger than 4 years of age. METHODS:This retrospective interventional case series included 14 microphthalmic eyes from 10 children who underwent congenital cataract surgery with primary intraocular lens implantation younger than 4 years of age. Seven patients had bilateral cataracts (11 eyes met the study's inclusion criteria) and 3 patients had unilateral cataract. Patients' medical charts were reviewed to obtain information regarding the preoperative and postoperative ophthalmological examination. Main outcome measures were intraocular pressure (IOP), best-corrected visual acuity, and intraoperative and postoperative complications. RESULTS: Mean age at the time of surgery was 21.7 ± 2.9 months. Mean ocular axial length was 19.2 ± 0.9 mm. Mean preoperative IOP was 9.7 ± 1.7 mmHg and 10.3 ± 3.1 mmHg on final follow-up (P=0.18). There were no intraoperative complications. Two (15.4%) eyes developed secondary visual axis opacification, of which only one needed to be reoperated due to significantly decreased vision (0.5 logMAR). Preoperative and postoperative best-corrected visual acuity was 2.09 ± 0.97 logMAR and 0.38 ± 0.08 logMAR in bilateral cases and 1.83 ± 1.04 logMAR and 0.42 ± 0.13 logMAR in unilateral cases, respectively. CONCLUSION: Primary intraocular lens implantation in congenital cataract surgery in microphthalmic eyes resulted in a significant best-corrected visual acuity improvement with no intraoperative complications and minimal postoperative complications.